The Problems of Reading Arabic Text in Terms of Phonological Aspects (Case Study in Fifth Grade Students of SD Qurrota A’yun Babadan Bantul DIY Academic Year 2020/2021) - Arina Nur Sofiana; Nur Hapsari Paramitha; Nurul Huda (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2021)
This study aims to determine the problems of fifth-grade students of SD Qurrota A'yun in reading Arabic texts in terms of phonological aspects, to find out the efforts made by Arabic teachers in overcoming these problems, and to find out the ideal concept of learning Arabic phonology at the elementary school level. This research is a case study and field research conducted at SD Qurrota A'yun, Babadan, Bantul, DIY. The data collection used is the acquisition of qualitative data. The research subjects were the principal, Arabic teacher, and fifth-grade students of SD Quurota A'yun. Sampling was carried out using non-probability sampling in the form of purposive samples (purposed samples). They are collecting data using the method of observation, interviews, and documentation. The results of the study indicate that there are problems with reading Arabic text in students' Arabic learning in terms of phonology, are consists of phonetic aspects (in the form of vocal and consonant problems) and phonemic aspects (in the form of incorrect phonological pronunciation so that it can change the meaning of Arabic vocabulary). For this reason, teachers try to overcome this by collaborating Arabic lessons with Al-Qur'an lessons. The ideal concept of learning Arabic phonology at the elementary school level is inseparable from learning the Qur'anic tahsin. Keywords: Reading Problems, Arabic Language, Arabic Text, Phonology. Abstrak Penelitian ini bertujuan untuk mengetahui problematika siswa kelas V SD Qurrota A’yun dalam membaca teks Arab ditinjau dari aspek fonologi, untuk mengetahui usaha yang dilakukan guru bahasa Arab dalam mengatasi problematika tersebut, dan untuk mengetahui konsep ideal pembelajaran fonologi bahasa Arab pada tingkat sekolah dasar. Penelitian ini merupakan penelitian studi kasus dan lapangan yang dilakukan di SD Qurrota A’yun, Babadan, Bantul, DIY. Pemerolehan data yang digunakan yaitu dengan pemerolehan data kualitatif. Subjek penelitian yaitu kepala sekolah, guru bahasa Arab, dan peserta didik kelas V SD Quurota A’yun. Pengambilan sampel dilakukan dengan menggunakan non probability sampling berup purposive sample (sampel bertujuan). Pengumpulan data menggunakan metode observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa terdapat problematika membaca teks Arab dalam pembelajaran bahasa Arab siswa ditinjau dari segi fonologi yaitu terdiri dari aspek fonetik (berupa problematika vokal dan konsonan) dan aspek fonemik (berupa pengucapan fonologi yang kurang tepat sehingga bisa merubah makna dari kosakata bahasa Arab). Untuk itu, guru berupaya mengatasi hal tersebut dengan mengkolaborasikan pelajaran bahasa Arab dengan pelajaran Al-Qur’an. Konsep ideal pembelajaran fonologi bahasa Arab pada tingkat sekolah dasar yaitu tidak lepas dari pembelajaran tahsin Al-Qur’an. Keywords: Problematika Membaca, Bahasa Arab, Teks Arab, Fonologi.